(untitled) (Proceedings of the Global Public Health Conference, 2020)
Objectives: This study aimed to identify knowledge gaps in the clinical skills of traditional birth attendants TBAs to address them and subsequently help to improve the outcomes of home deliveries in rural Guatemala. An implementation of a basic training program addressed the knowledge gaps. Design and Method: A qualitative study consisting of interviews with 6 practicing traditional birth attendants (TBAs) utilizing qualitative analysis followed by a training session for prenatal care Setting: Q’echi-Mayan speaking communities in a lake. Izabel and hills regions of Guatemala Findings: Significant deficits in knowledge of the TBAs regarding the physiology of pregnancy and skills for management of common high-risk conditions, such as hyperemesis and pregnancy-induced hypertension, that require referral to other skilled birth attendants (SBAs) and to manage these situations early to prevent complications. This study helped to identify barriers faced by traditional birth attendants in the remote Mayan communities. A program that employed a teaching tool based on WHO recommendations were employed to teach TBAs, which was well accepted by TBAs. Results/Conclusions: Traditional birth attendants reported significant knowledge gaps. The study emphasizes the importance of supplementing the training of TBAs with additional periodic training and refreshers.